Microbial wastewater treatment - Shah, Maulin P.; Roguez-Couto, Susana (Elsevier, 2019)
Microbial Wastewater Treatment focuses on the exploitation of microorganisms as decontaminating tools to treat polluted wastewater, a worldwide concern. Microorganism-based processes are seen as promising technologies to treat the ever-increasing problem of polluted wastewater. The book covers recently developed process technologies to solve five major trends in the field of wastewater treatment, including nutrient removal and recovery, trace organic compounds, energy saving and production, sustainability and community involvement.